A method for preparing 5-hydroxymethylfurfural
Patent Information
- Application Number
- CN202410248671.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-05
AI Technical Summary
In existing technologies, the conversion of cellulose to 5-hydroxymethylfurfural has a low yield and produces many byproducts, making it difficult to achieve efficient one-pot synthesis.
A modified UiO-66-NH2(Hf/Zr) catalyst was used to heat the reaction in a two-phase system of water and organic phases. By controlling the metal doping ratio and reaction time, cellulose was directly converted into 5-hydroxymethylfurfural.
It significantly improved the yield of 5-hydroxymethylfurfural, simplified the preparation process, and improved catalytic efficiency.
Smart Images

Figure CN118108686B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to catalyst preparation methods and their applications, specifically a method for preparing 5-hydroxymethylfurfural. Background Technology
[0002] 5-Hydroxymethylfurfural (HMF) is an important platform chemical that can be used to prepare various high-value-added bio-based chemical derivatives, such as 2,5-furandicarboxylic acid (FDCA), 2,5-dihydroxymethylfuran (DHMF), and 5-hydroxymethylfuranic acid (HMFA), through oxidative hydrogenation and condensation. While most platform compounds have a chain structure, HMF is the only one with a cyclic structure, exhibiting good structural stability and high strength. Furthermore, the oxygen atoms in its furan ring may endow materials with unique properties, thus HMF possesses great development potential and application prospects.
[0003] Simple monosaccharides like fructose and glucose can typically be used as reactants to produce large quantities of HMF. However, monosaccharides not only serve as resources in the food industry but are also expensive and difficult to obtain. In contrast, cellulose is a more suitable material for synthesizing HMF, offering advantages such as abundance, affordability, and inedibility. Cellulose is the most abundant renewable polymer on Earth and a valuable renewable resource. The challenges in developing cellulose for HMF production include improving HMF yield and cellulose conversion, as well as minimizing byproduct generation, which drives the search for optimal catalysts.
[0004] Metal-organic frameworks (MOFs) are a unique class of porous crystalline materials that have been extensively studied over the past two decades due to their inherent design flexibility and potential applications in gas adsorption / separation, luminescence and sensing, electrochemistry, and catalysis. Importantly, the structure, pore size, and other properties of MOFs can be tuned by modifying metal nodes and organic ligands, thereby optimizing these properties and achieving excellent catalytic performance in a variety of reactions. The UiO-66-NH2 framework is a powerful motif, well-suited for network-like functionalization and modification.
[0005] Synthesizing functional MOF catalysts for cellulose conversion is a promising option. Currently, while there are numerous reports on the use of MOF catalysts to convert glucose to HMF, there is relatively little attention paid to cellulose conversion. UiO-66 is a representative MOF, a zirconium-based catalyst containing a phenyl-1,4-dicarboxylic acid ester (BDC) linker, exhibiting high structural thermal stability (up to 500℃). Zhao et al. synthesized a PHs precursor using Pickering HIPEs as a template, which, after sulfonation, yielded PHs-SO3H. They then attached UiO-66-NH2 to PHs-SO3H to prepare a hierarchical porous catalyst, PHs-SO3H@UiO-66-NH2. They found that the addition of UiO-66-NH2 increased the yield of HMF, indicating that UiO-66-NH2 not only provided a microporous structure, but also that the amino groups in UiO-66-NH2 had a very effective effect on the isomerization of glucose, which is a very important step in the catalytic process of cellulose to 5-HMF (ZHAO J, ZHANG Y, WANG K, et al. Development of Hierarchical Porous MOF‐Based Catalyst of UiO‐66(Hf) and Its Application for 5‐Hydroxymethylfurfural Production from Cellulose [J]. ChemistrySelect, 2018,3(41): 11476-85.). Wei et al. prepared a novel macroporous polymer catalyst with acid-base bifunctional linkage using Pickering HIPEs as templates and MOFs (UiO-66-SO3H and UiO-66-NH2), and studied its performance in cellulose conversion in [EMIM]Cl solvent. To establish the correlation between catalyst structure and catalytic activity, key parameters in the catalyst preparation process were optimized, such as surfactant dosage, internal phase volume fraction, and the mass ratio of UiO-66-SO3H:UiO-66-NH2. They ultimately found that the optimal catalyst had an internal phase volume fraction of 80%, a surfactant dosage of 1.5% (mass), and (m... UiO-66-SO3H :m UiO-66-NH2Under the catalysis of a 1:5 ratio catalyst, the reaction time was 130℃ for 3 h, and the highest HMF yield was 40.5% (WEI Y, ZHANG Y, LI B, et al. Facile synthesis of metal-organic frameworks embedded in interconnected macroporous polymer as a dual acid-basebifunctional catalyst for efficient conversion of cellulose to 5-hydroxymethylfurfural [J]. Chinese Journal of Chemical Engineering, 2022, 44:169-81.). The conversion of cellulose to HMF requires a hydrolysis step, using a Bronsted acid catalyst to produce glucose, followed by an isomerization reaction using a Lewis acid / base catalyst to convert glucose to fructose. Finally, the fructose is dehydrated to HMF using a Bronsted acid catalyst. Compared to one-pot synthesis, the synthesis of HMF through multiple reactions is less energy-efficient and time-efficient. Therefore, the focus of this research is to find an efficient catalytic system for the direct one-pot synthesis of HMF from cellulose, thereby improving efficiency and reducing waste. Summary of the Invention
[0006] Purpose of the invention: In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing 5-hydroxymethylfurfural with adjustable catalytic performance, high catalytic activity, high yield, and one-pot synthesis.
[0007] Technical solution: The present invention provides a method for preparing 5-hydroxymethylfurfural, comprising the following steps: using cellulose as raw material, adding a modified catalyst under the condition of a water and organic phase biphase system, and heating to react to obtain 5-hydroxymethylfurfural, wherein the modified catalyst is a UiO-66-NH2(Hf / Zr) catalyst.
[0008] Furthermore, the water and organic phase biphase system is any one of H2O / THF, H2O / 2-butanol, H2O / MIBK, and H2O / MeTHF.
[0009] Furthermore, the mass ratio of the modified catalyst to cellulose is 5~100:50~200.
[0010] Furthermore, the temperature for heating the reaction is 170~200℃, and the reaction time is 1~6 h.
[0011] Furthermore, the preparation method of the UiO-66-NH2(Hf / Zr) catalyst includes the following steps:
[0012] Step 1: Weigh out hafnium chloride, zirconium chloride and acid conditioner, then slowly pour in N,N-dimethylformamide and mix thoroughly by ultrasonication to obtain solution A;
[0013] Step 2: Weigh the ligand and add it evenly to solution A, then sonicate until the mixture is homogeneous;
[0014] Step 3: Perform a hydrothermal reaction on the solution obtained in Step 2;
[0015] Step four: Centrifuge the reaction solution obtained in step three to obtain precipitates of different color depths. Wash twice to remove unreacted ligands and solvents, and vacuum dry overnight at room temperature to obtain the UiO-66-NH2(Hf / Zr) catalyst.
[0016] Furthermore, in step one, the acid regulator is any one of acetic acid, octanoic acid, lauric acid, and myristic acid. The mass ratio of hafnium to zirconium in hafnium chloride and zirconium chloride is 0.2~5.
[0017] Furthermore, in step two, the ligand is 2-aminoterephthalic acid.
[0018] Furthermore, in step three, the hydrothermal reaction temperature is 100~120℃, and the time is 2~7 days.
[0019] Furthermore, in step four, washing involves removing unreacted ligands with N,N-dimethylformamide and removing the solvent with methanol.
[0020] Preparation principle: Using a solvothermal method (hydrothermal method), the solvent, metal salt, and organic ligand are mixed in a certain proportion and transferred to a high-temperature and high-pressure reactor. After reacting at a certain temperature for 24 hours, the modified catalyst is obtained through washing and drying. Considering that UiO-66 (Zr) and UiO-66 (Hf) should have similar physical properties, since both Zr and Hf belong to Group IV elements, and considering the dissociation energy of the Hf−O bond (802 kJ / mol), [further details are needed]. −1 The dissociation energy is higher than that of the Zr−O bond (776 kJ mol). −1 Hf should have stronger oxygen affinity, and the Hf-containing secondary building blocks (SBUs) of UiO-66 The group may be more complex than the SBUs in UiO-66(Zr). The group possesses stronger Brønsted acid site functionality, a unique characteristic that may enable Hf-MOFs to exhibit superior performance in catalytic and gas separation applications. Therefore, considering the tunability of MOFs, defect modulation is employed. Specifically, metal defects are added before the preparation of the metal-organic framework material. This involves adding metal ions to the precursor used in the preparation of the metal-organic framework material. This metal precursor competes with the original precursor, thus generating metal defects. Hafnium chloride, zirconium chloride, and octanoic acid were weighed into a 100 mL polytetrafluoroethylene solvothermal reactor liner. Then, 60 mL of N,N-dimethylformamide was slowly poured into the liner. Next, the ligand 2-aminoterephthalic acid was weighed into the above mixed solution. The mixture was ultrasonically stirred for approximately 15 minutes to obtain a homogeneous precursor. This precursor was then transferred to a 120°C oven for drying for 48 hours, followed by subsequent washing, drying, and other post-treatment processes. This method not only utilizes the advantages of Hf element to give modified MOFs better catalytic effects, but also saves preparation time and improves preparation efficiency by adding metal ions to the precursor used before preparing metal-organic framework materials and adopting a one-step hot solvent method.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0022] 1. The modified catalyst obtained was prepared by a one-step solvothermal method, which provides an excellent opportunity to customize its catalytic performance by taking advantage of the high tunability of MOF nodes / linkers;
[0023] 2. Considering the tunability of MOFs, the metal-oxygen clusters in UiO-66-NH2 can be used in Zr with similar physicochemical properties. 4 + and Hf 4+ By exchanging elements, novel metal-doped UiO-66-NH2 (Hf / Zr) nanoparticles were synthesized;
[0024] 3. By adjusting different doping ratios, modified catalysts with high catalytic activity were prepared, and the amount of modified catalyst and reaction time were adjusted to promote the catalytic conversion of cellulose and significantly improve the yield of 5-hydroxymethylfurfural. Attached Figure Description
[0025] Figure 1 This is a reaction process diagram of the preparation of the UiO-66-NH2(Hf / Zr) material and its biomass catalytic performance study of the present invention;
[0026] Figure 2 This is the X-ray diffraction pattern of the UiO-66-NH2(Hf / Zr) sample of Example 4 of the present invention;
[0027] Figure 3This is the nitrogen adsorption-desorption curve of the UiO-66-NH2(Hf / Zr) sample in Example 4 of this invention;
[0028] Figure 4 This is the NH3-TPD diagram of the UiO-66-NH2(Hf / Zr) sample in Example 4 of this invention;
[0029] Figure 5 This is a yield diagram of 5-HMF obtained in Examples 1, 4, and 7 of the present invention. Detailed Implementation
[0030] Unless otherwise specified, the experimental methods described in the examples are conventional methods; and the reagents and materials are commercially available unless otherwise specified.
[0031] Example 1
[0032] like Figure 1 A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0033] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0034] (1) Weigh 0.046 g of hafnium chloride, 0.328 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, with m(Hf):m(Zr) = 1:5; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0035] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0036] (3) The obtained solution is placed in a solvothermal reactor and placed in an oven at 120°C for 2 days.
[0037] (4) The obtained reaction solution is centrifuged to obtain a precipitate. It is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. Then it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-1(Hf / Zr).
[0038] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0039] 100 mg of cellulose, 50 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 190 °C. The mixture was magnetically stirred and heated for 2 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0040] The yield of 5-hydroxymethylfurfural in this example was 29.72%.
[0041] Example 2
[0042] A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0043] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0044] (1) Weigh 0.101 g of hafnium chloride, 0.288 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, m(Hf):m(Zr) = 2:4; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0045] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0046] (3) The obtained solution is placed in a solvothermal reactor and placed in an oven at 120°C for 2 days.
[0047] (4) The obtained reaction solution is centrifuged to obtain a precipitate. The precipitate is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. After that, it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-2(Hf / Zr).
[0048] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0049] 100 mg of cellulose, 50 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 190 °C. The mixture was magnetically stirred and heated for 2 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0050] The yield of 5-hydroxymethylfurfural in this embodiment was 36.91%.
[0051] Example 3
[0052] A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0053] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0054] (1) Weigh 0.168 g of hafnium chloride, 0.239 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, m(Hf):m(Zr) = 3:3; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0055] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0056] (3) The obtained solution is placed in a solvothermal reactor and placed in an oven at 120°C for 2 days.
[0057] (4) The obtained reaction solution is centrifuged to obtain a precipitate. It is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. Then it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-3(Hf / Zr).
[0058] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0059] 100 mg of cellulose, 50 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 190 °C. The mixture was magnetically stirred and heated for 2 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0060] The yield of 5-hydroxymethylfurfural in this example was 37.47%.
[0061] Example 4
[0062] A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0063] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0064] (1) Weigh 0.251 g of hafnium chloride, 0.179 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, m(Hf):m(Zr) = 4:2; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0065] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0066] (3) The obtained solution is placed in a solvothermal reactor and placed in an oven at 120°C for 2 days.
[0067] (4) The obtained reaction solution is centrifuged to obtain a precipitate. It is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. Then it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-4(Hf / Zr).
[0068] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0069] 100 mg of cellulose, 50 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 190 °C. The mixture was magnetically stirred and heated for 2 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0070] The yield of 5-hydroxymethylfurfural in this example was 46.02%.
[0071] like Figure 2 The XRD patterns show that the diffraction peaks of UiO-66-NH2(Hf / Zr) material are in the same position as those of UiO-66-NH2, and the peaks are sharp. This indicates that the addition of Hf element did not change the crystal phase of UiO-66-NH2, and the original crystal lattice structure was preserved.
[0072] Figure 3 The N2 adsorption-desorption isotherms of UiO-66-NH2(Hf / Zr) are presented. The results show that the adsorption capacity increases rapidly in the low relative pressure region of 0–0.1, reaching a maximum with increasing pressure, similar to a typical Type I adsorption isotherm for microporous or near-microporous structures. When the relative pressure increases from 0.9 to 1.0, the adsorption capacity also increases sharply, possibly due to interparticle condensation. Within the relative pressure range of 0.1–0.9, the adsorption capacity shows a slow upward trend, indicating the presence of a small amount of mesoporous material. The test sample exhibits a distinct H4-type hysteresis loop near P / P0 (0.9–1.0), mainly due to the aggregation of small-sized MOF particles. The results indicate that UiO-66-NH2(Hf / Zr) has a microporous (with a small amount of mesoporous) structure.
[0073] The acidity of the prepared UiO-66-NH2(Hf / Zr) catalyst was evaluated by NH3-TPD analysis. The temperatures of 350-500℃, 250-350℃, and 150-250℃ were divided into strong, medium, and weak acid sites. The analytical results are as follows: Figure 4 As shown, the modified UiO-66-NH2(Hf / Zr) exhibits significantly higher acid strength than UiO-66-NH2. As a porous bifunctional acid catalyst, its catalytic activity is enhanced by improving both the porous structure and active sites of the solid acid catalyst, thus promoting the yield of 5-HMF.
[0074] Example 5
[0075] A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0076] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0077] (1) Weigh 0.357 g of hafnium chloride, 0.102 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, m(Hf):m(Zr) = 5:1; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0078] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0079] (3) The obtained solution is placed in a solvothermal reactor and placed in an oven at 120°C for 2 days.
[0080] (4) The obtained reaction solution is centrifuged to obtain a precipitate. It is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. Then it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-5(Hf / Zr).
[0081] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0082] 100 mg of cellulose, 50 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 190 °C. The mixture was magnetically stirred and heated for 2 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0083] The yield of 5-hydroxymethylfurfural in this example was 27.54%.
[0084] Example 6
[0085] The remaining steps in this embodiment are the same as in Example 4, except that the amount of modified catalyst is replaced with 75 mg.
[0086] The yield of 5-hydroxymethylfurfural in this example was 47.61%.
[0087] Example 7
[0088] The remaining steps in this embodiment are the same as in embodiment 6, except that the magnetic stirring and heating time is 4 hours.
[0089] The yield of 5-hydroxymethylfurfural in this example was 50.61%.
[0090] Example 8
[0091] A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0092] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0093] (1) Weigh 0.101 g of hafnium chloride, 0.288 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, m(Hf):m(Zr) = 0.5; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0094] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0095] (3) The obtained solution is placed in a solvothermal reactor and placed in an oven at 100°C for 7 days.
[0096] (4) The obtained reaction solution is centrifuged to obtain a precipitate. It is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. Then it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-8(Hf / Zr).
[0097] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0098] Weigh out 50 mg of cellulose, 5 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent. Place the reaction mixture in an oil bath at 170 °C, stir magnetically, and heat for 6 h. After the reaction is complete, allow the reactor to cool naturally to room temperature and remove the supernatant. Separate the resulting solution using a centrifuge and filter out the organic phase. The centrifuged product is used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product can be quantitatively obtained from the standard curve, and the HMF yield can be calculated.
[0099] Example 9
[0100] A method for preparing 5-hydroxymethylfurfural includes the following steps:
[0101] Preparation of S1, UiO-66-NH2(Hf / Zr) catalyst:
[0102] (1) Weigh 0.168 g of hafnium chloride, 0.239 g of zirconium chloride, and 6 mL of octanoic acid into a polytetrafluoroethylene solvothermal reactor liner, m(Hf):m(Zr) = 1; then measure 60 mL of N,N-dimethylformamide and slowly pour it into the liner, sonicate for 10 min to mix evenly, and obtain solution A;
[0103] (2) Weigh 0.562g of the ligand 2-aminoterephthalic acid and add it evenly to solution A, and sonicate for 20min until it is evenly mixed.
[0104] (3) The obtained solution was placed in a solvothermal reactor and placed in an oven at 110°C for 4 days.
[0105] (4) The obtained reaction solution is centrifuged to obtain a precipitate. It is washed twice with N,N-dimethylformamide to remove unreacted ligands and several times with methanol to remove solvent. Then it is vacuum dried overnight at room temperature to obtain UiO-66-NH2(Hf / Zr) catalyst, denoted as UN-9(Hf / Zr).
[0106] S2 undergoes a catalytic conversion from cellulose to 5-HMF in an aqueous organic-phase biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0107] 200 mg of cellulose, 100 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 200 °C. The mixture was magnetically stirred and heated for 1 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0108] In summary, this invention provides the preparation of modified UiO-66-NH2(Hf / Zr) materials and the study of their biomass catalytic performance. This catalyst is prepared via a one-step solvothermal method, and the high tunability of MOF nodes / linkers provides an excellent opportunity to customize its catalytic performance. Considering the tunability of MOFs, the metal-oxygen clusters in UiO-66-NH2 can be used in Zr with similar physicochemical properties. 4+ and Hf 4+ Novel metal-doped UiO-66-NH2 (Hf / Zr) nanoparticles were synthesized by exchanging between different doping ratios. By adjusting the doping ratios, highly active modified catalysts were prepared, and the amount of modified catalyst and reaction time were optimized to promote the catalytic conversion of cellulose and significantly improve the yield of 5-hydroxymethylfurfural.
[0109] Comparative Example 1
[0110] The catalyst preparation method of this comparative example is the same as that of Example 4, except that the amount of substrate used in the reaction performance test is changed to 75 mg.
[0111] Catalytic conversion of cellulose to 5-HMF occurs in an aqueous organic biphase system under the catalysis of UiO-66-NH2(Hf / Zr) catalyst.
[0112] 75 mg of cellulose, 50 mg of modified catalyst, 300 mg of NaCl, 1 mL of H₂O, and 4 mL of THF biphase solvent were weighed and placed in an oil bath at 190 °C. The mixture was magnetically stirred and heated for 2 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature, and the supernatant was removed. The resulting solution was separated using a centrifuge and filtered to remove the organic phase. The centrifuged product was used for subsequent quantitative analysis. Using commercially available HMF as a standard, the peak position and retention time of HMF were determined, and a 5-HMF standard curve was plotted by measuring the peak area at different HMF concentrations. The final HMF concentration in the product could be quantitatively obtained from the standard curve, and the HMF yield could be calculated.
[0113] The yield of 5-hydroxymethylfurfural in this comparative example was 40.23%.
[0114] Comparative Example 2
[0115] The remaining steps of this comparative example are the same as those of comparative example 1, except that the substrate dosage is 150 mg.
[0116] The yield of 5-hydroxymethylfurfural in this comparative example was 36.66%.
[0117] Comparative Example 3
[0118] The remaining steps of this comparative example are the same as those of comparative example 2, except that the reaction temperature is 200℃.
[0119] The yield of 5-hydroxymethylfurfural in this comparative example was 31.65%.
[0120] Comparative Example 4
[0121] The remaining steps of this comparative example are the same as those of comparative example 3, except that the volumes of water and organic phase are 1 ml and 3 ml, respectively.
[0122] The yield of 5-hydroxymethylfurfural in this comparative example was 37.31%.
[0123] Comparative Example 5
[0124] The remaining steps of this comparative example are the same as those of comparative example 4, except that the volumes of water and organic phase are 1 ml and 5 ml, respectively.
[0125] The yield of 5-hydroxymethylfurfural in this comparative example was 28.40%.
Claims
1. A method for preparing 5-hydroxymethylfurfural, characterized in that: Includes the following steps: Using cellulose as a raw material, a modified catalyst was added under the condition of a two-phase system of water and organic phase, and the reaction was heated to obtain 5-hydroxymethylfurfural. The modified catalyst was a UiO-66-NH2(Hf / Zr) catalyst. The preparation method of the UiO-66-NH2(Hf / Zr) catalyst includes the following steps: Step 1: Weigh out hafnium chloride, zirconium chloride, and acid conditioner, then slowly pour in N,N-dimethylformamide and mix thoroughly by ultrasonication to obtain solution A; the mass ratio of hafnium to zirconium in hafnium chloride and zirconium chloride is 0.2~5; Step 2: Weigh out the ligand and add it evenly to solution A, then sonicate until the mixture is homogeneous; Step 3: Perform a hydrothermal reaction on the solution obtained in Step 2; Step four: Centrifuge the reaction solution obtained in step three to obtain precipitates of different color depths. Wash twice to remove unreacted ligands and solvents, and vacuum dry overnight at room temperature to obtain the UiO-66-NH2(Hf / Zr) catalyst.
2. The method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: The water and organic phase biphase system is any one of H2O / THF, H2O / 2-butanol, H2O / MIBK, and H2O / MeTHF.
3. The method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: The mass ratio of the modified catalyst to cellulose is 5~100:50~200.
4. The method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: The heating reaction is carried out at a temperature of 170~200℃ for a time of 1~6 h.
5. The method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: In step one, the acid regulator is any one of acetic acid, caprylic acid, lauric acid, and myristic acid.
6. The method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: In step two, the ligand is 2-aminoterephthalic acid.
7. The method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: In step three, the hydrothermal reaction temperature is 100~120℃ and the time is 2~7 days.
8. A method for preparing 5-hydroxymethylfurfural according to claim 1, characterized in that: In step four, washing involves removing unreacted ligands with N,N-dimethylformamide and removing the solvent with methanol.
